2018
DOI: 10.1186/s40168-018-0477-5
|View full text |Cite
|
Sign up to set email alerts
|

The effect of the timing of exposure to Campylobacter jejuni on the gut microbiome and inflammatory responses of broiler chickens

Abstract: BackgroundCampylobacters are an unwelcome member of the poultry gut microbiota in terms of food safety. The objective of this study was to compare the microbiota, inflammatory responses, and zootechnical parameters of broiler chickens not exposed to Campylobacter jejuni with those exposed either early at 6 days old or at the age commercial broiler chicken flocks are frequently observed to become colonized at 20 days old.ResultsBirds infected with Campylobacter at 20 days became cecal colonized within 2 days of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
145
3
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 102 publications
(162 citation statements)
references
References 58 publications
12
145
3
2
Order By: Relevance
“…The provision of dietary GOS increased the density of goblet cells populating ileal villi in the developing chicken gut. Goblet cell increases were accompanied by significant differences in the villus height and crypt depth at 15 da, a period when transitions in the development of the chicken microbiota from a juvenile to a mature composition are observed (70)(71)(72). Using molecular methods, we have demonstrated a significant correlation between the market weight of chickens at 35 da and the cecal abundance of a specific L. johnsonii isolate identified as differentially abundant in the juvenile microbiota of GOS-fed birds.…”
Section: Resultsmentioning
confidence: 84%
See 1 more Smart Citation
“…The provision of dietary GOS increased the density of goblet cells populating ileal villi in the developing chicken gut. Goblet cell increases were accompanied by significant differences in the villus height and crypt depth at 15 da, a period when transitions in the development of the chicken microbiota from a juvenile to a mature composition are observed (70)(71)(72). Using molecular methods, we have demonstrated a significant correlation between the market weight of chickens at 35 da and the cecal abundance of a specific L. johnsonii isolate identified as differentially abundant in the juvenile microbiota of GOS-fed birds.…”
Section: Resultsmentioning
confidence: 84%
“…Reverse Transcription was performed with 1 g of RNA, SuperScript II (Invitrogen Life Technologies, Carlsbad, USA.) and random hexamers as described previously (70).…”
Section: Rna Isolation and Rt-qpcr Of The Cytokines And Chemokinesmentioning
confidence: 99%
“…This creates a brief window at 439 the point in which maternal antibodies have depleted, whereby any new strain 440 introduced is observed to quickly colonise and dominate the gut flora, suppressing other 441 strains (see Figure 10C). This hypothesis has been verified experimentally [39]. lower Campylobacter prevalence rate than commercial broiler flocks [41].…”
mentioning
confidence: 64%
“…First, the most apparent prediction is that the Campylobacter population is successfully 430 suppressed by the innate maternal antibodies (an experimentally observed 431 phenomenon [39]), until these antibodies are eventually removed from the system. At Campylobacter to emerge as an early dominating strain.…”
mentioning
confidence: 99%
“…Our pathway analysis also showed enrichment for other innate and adaptive immune related pathways in association with Campylobacter resistance. Of increased interest is the pathway related with IL-17 signalling since several previous studies suggested that IL-17 signalling and T H -17 responses play a role in resistance to Campylobacter colonisation in chickens following experimental inoculation [13, 16, 19, 56, 63, 64]. Future studies could seek to characterise the timing and magnitude of such responses in birds of predicted resistant or susceptible genotypes upon exposure.…”
Section: Discussionmentioning
confidence: 99%